Instrumentalundervisningens problem – en kritik af fraværet af instrumentalpædagogisk grundlagsforskning - Lyngseth, Øyvind (Studier i Pædagogisk Filosofi, 2018)
Abstract The article argues that there is a need for a thorough philosophical inquiry into the epistemological basis of instrumental teaching. This kind of inquiry has not previously been undertaken. The way in which practitioners within the instrumental-pedagogical field are often making subjective and individual references to taste (taste-argument) and tradition (tradition-argument) in order to legitimize the self-understanding of the instrumental-pedagogical field, is critiqued. Hans-Georg Gadamer’s Philosophical Hermeneutics and his opus magnum, Truth and Method, are primarily informing the hermeneutical and epistemological analysis and critique of the instrumental-pedagogical praxis. The aim of the article is not only to point to the absence of epistemological research, but also to sketch the foundation for a future constructive discussion about the cultivation of critical self-understanding of the instrumental-pedagogical field.